OPTIMASI KEMIRINGAN MAGNET PADA GENERATOR MAGNET PERMANEN KECEPATAN RENDAH FLUKS RADIAL - Irasari, Pudji; Kasim, Muhammad; Fitriana, - (LIPI Press, 2010)
Optimization of magnet skewing of 1 kW, 3 phase, 300 rpm permanent magnet generator has been conducted in this research. The optimization is carried out by simulating some position of the rotor magnet skewing (x). The defi nition of skewing in this experiment is the outer line of one pole that is appear due to the shifting of two magnet segments that forming the pole. The three skewing position that is analyzed are x1 = 16 mm, x2 = 21 mm, x3 = 25,6 mm. Those skewing positions result in different harmonic distortion (HD) and EMF voltage waveform. The experimental validation shows that the best characteristic is obtained at skewing of x = 21 mm with HD = 11.9% and has the most sinusoidal EMF voltage waveform.